La evaluación como instrumento para mejorar la calidad educativa: reflexiones sobre las últimas tendencias en los procesos de evaluación - Méndez Zamalloa, Guadalupe (2011)
The evaluation as an instrument of diagnosis, development and appraisal of educational actions currently needs to be taken into consideration by professors and academics of the education field. This article analyses the assessment of learning from a modern view emphasizing the auto evaluation and co evaluation, as well as the use of non-conventional evaluation instrLme nt s. The evaluation of teachers is widely analyzed, considering the latest developments in the country and the institutional evaluation, particularly appointed tothe accreditation.